Trans Equity Project: a multicomponent intervention to improve HIV prevention and care continua outcomes among men and women of transgender experience - Allysha C. Maragh-Bass; Elena Cyrus; Tatyana Woodard; Lekiah Lescott; Ashley French; Emily A. Arnold; Mallory O. Johnson; Omar Martinez (HIV Research & Clinical Practice, 2025)
Purpose Men and women of transgender experience encounter HIV-related health inequities based on race across the HIV care continua. We explored HIV prevention and care needs via focus groups, surveys, and Sexually Transmitted Infection (STI) testing experiences (N = 40); we supplemented this data via in-depth interviews with peer navigators. Methods This study was conducted from 2020 to 2022. Analyses included coding and descriptive statistics. Nearly 63% identified as Black, and 20% identified as Latinx. Nearly 90% of participants reported ever having HIV tests; 10% of participants tested positive for other STIs. Results Qualitative analyses yielded three core intervention components for men and women of transgender experience: (1) Comprehensive Trans Care; (2) Community, Mentorship, and Support; and (3) Life Skills and Professional Development. Study participants, community and scientific advisory board members agreed on the need for a peer-led, group-level intervention in English and Spanish. Conclusion These needs and priorities are conducive to future interventions which build community agency, structural approaches, and health equity centered on men and women of transgender experience of color.